MENINGKATKAN PERANAN GURU PROFESIONAL DALAM MENGHADAPI ERA REVOLUSI INDUSTRI 4.0 - Suyati, Suyati (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The teacher's role and teacher's duties as one of the determinant factors for the success of education, especially in facing education in the era of industrial revolution 4.0. The existence and improvement of teacher professionalism is a very important discourse. Education in the industrial revolution era 4.0 demands a good and professional management of education. Professional teachers emphasize the ability of teachers to transfer knowledge, the ability of teachers to design strategies, and the ability of teachers to implement their learning.